Allelopathic effects of Cynara cardunculus L. leaf aqueous extracts on seed germination of some Mediterranean weed species - Scavo, Aurelio; Restuccia, Alessia; Pandino, Gaetano; Onofri, Andrea; Mauromicale, Giovanni (Italian Journal of Agronomy, 2018)
It is known that the presence of weeds causes serious losses to the agricultural production, both in quantitative and qualitative terms. The major problem in modern agriculture is the environmental impact of synthetic herbicides and the increase in herbicide- resistant weed species. Allelopathic compounds can be used to develop a sustainable weed management system based on natural products. The objective of this study was to evaluate the allelopathic potential of leaf aqueous extracts (40 and 80%) obtained from Cynara cardunculus L. plant species on seed germination and mean germination time of six common weeds in Mediterranean agroecosystems: Amaranthus retroflexus L., Diplotaxis erucoides (L.) DC., Portulaca oleracea L., Lavatera arborea L., Brassica campestris L. and Solanum nigrum L. Effects varied with the weed species and the concentrations of the extracts. On average, the aqueous leaf extracts significantly reduced the final percentage of seed germination compared to the control for A. retroflexus (–58.1%), D. erucoides (–43.9%) and P. oleracea (–42.5%). The rate of germination decreased with increasing extract concentration. In C. cardunculus L. var. sylvestris the autoallelopathic activity also was demonstrated. These results are very promising in order to produce a bioherbicide based on C. cardunculus allelochemicals.